Impact of temperature and duration variations on the quality of acacia bark tannin for in-vitro treatment of sheep diarrhoea - Supardan Atep Dian; Nuraini Febrian; Ramdhan Mohamad Alief; Sholeha Novia Amalia; Azami Mohammad Saifulddinbin Mohd; Listiasari Faranita Ratih; Muliawati Nindya Tri; Laila Farida; Resmeiliana Ika; Sujamoko Tekad Urip Pambudi (E3S Web of Conferences)
Sheep frequently experience diarrhoea. An efficacious therapeutic approach involves the utilisation of herbal medicine, which frequently contains tannins owing to its antibacterial and antidiarrheal characteristics. Acacia bark is an important resource due to its high tannin content, which typically ranges from 18% to 25%. The objective of this study is to investigate the impact of varying extraction temperatures and durations on the quality of tannins, as well as to evaluate the efficacy of tannin extracts as a treatment for diarrhoea in sheep using in vitro methods. The extraction method used is hot water extraction (HWE), with temperatures set at 40, 60, and 80 °C and extraction durations of 45 and 60 minutes. The results demonstrated that the most favourable extraction conditions were at a temperature of 80 °C for a duration of 60 minutes. This resulted in a phenol content of 9.22 mg/L GAE, total tannins of 6.77 mg/mL, condensed tannins of 1.54 mg/mL, and hydrolyzable tannins of 5.23 mg/mL. Lab tests have demonstrated that the tannin extract is effective in treating diarrhoea in sheep. The highest concentration of 100% showed the most substantial inhibitory zone against E. coli bacteria. Therefore, the optimal amount of tannin to administer to sheep is calculated to be 10 grammes per 25 kilogrammes of body weight (BW).